عبد العزيز الفرهارويّ ومخطوطته "التمیيز": دراسة تمهيدية (Al-Qamar, 2020)
‘Abdul-‘Azīz Firhārvī (1206AH-1239AH) is one of the leading scholars of the subcontinent. Graduating from a seminary in Multan, Firhārvī modernized dozens of sciences and recorded his scholarly achievements. Discussing and arguing in an art related to its subject; demonstrates his speciality, which is extinct today. He has been writing on Tafsīr, Philosophy, ʻIlm al-kalām and other Islamic sciences. He produced more than hundred valuable writings. Only a few of his works have published while the rest are in manuscript form. One of his remarkable manuscripts is al-Tamyīz. The present paper centres a brief exploratory study of ‘Abd al-‘Azīz Firhārvī and his achievements particularly Al-tamyīz, which mainly deals with ʻIlm al-Kalām and Philosophy. This study will come to light the comprehensiveness and universality of this outstanding work. It will also encourage the new researchers to bring to the light Firhārvī’s other scholarly achievements.
Keywords: Abd al-‘Azīz Firhārvī; al-Tamyīz